Research Advances in Graphene Oxide Composites for Uranium Adsorption - LIU Peng; RUAN Hui; XUE Yun; MA Fu-qiu (He huaxue yu fangshe huaxue, 2023)
Due to its excellent adsorption properties, graphene oxide has attracted great attention in the field of radioactive wastewater treatment. The adsorption properties of graphene oxide can be further improved with functional modification. The paper introduces the adsorption properties and mechanism of graphene oxide for uranium. According to different modification methods, graphene oxide composites are divided into covalently functionalized composites and non-covalently functionalized composites. The adsorption properties and separation and recovery ability of covalently functionalized composites and non-covalently functionalized composites for uranium are comprehensive comparied. It is pointed out that the combination of these two modification methods is expected to be the key research direction of graphene oxide composite adsorption materials in the future.